Encapsulation of Cadmium Selenide Nanocrystals in Biocompatible Nanotubes: DFT Calculations, X‐ray Diffraction Investigations, and Confocal Fluorescence Imaging. Issue 2 (18th January 2018) - Calatayud, David G.; Ge, Haobo; Kuganathan, Navaratnarajah; Mirabello, Vincenzo; Jacobs, Robert M. J.; Rees, Nicholas H.; Stoppiello, Craig T.; Khlobystov, Andrei N.; Tyrrell, Rex M.; Como, Enrico Da; Pascu, Sofia I.
Abstract: The encapsulation of CdSe nanocrystals within single‐walled carbon nanotube (SWNT) cavities of varying dimensions at elevated temperatures under strictly air‐tight conditions is described for the first time. The structures of CdSe nanocrystals under confinement inside SWNTs was established in a comprehensive study, combining both experimental and DFT theoretical investigations. The calculated binding energies show that all considered polymorphs [(3:3), (4:4), and (4:2)] may be obtained experimentally. The most thermodynamically stable structure (3:3) is directly compared to the experimentally observed CdSe structures inside carbon nanotubes. The gas‐phase DFT‐calculated energy difference between "free" 3:3 and 4:2 structures (whereby 3:3 models a novel tubular structure in which both Cd and Se form three coordination, as observed experimentally for HgTe inside SWNT, and 4:2 is a motif derived from the hexagonal CuI bulk structure in which both Cd and Se form 4 or 2 coordination) is surprisingly small, only 0.06 eV per formula unit. X‐ray powder diffraction, Raman spectroscopy, high‐resolution transmission electron microscopy, and energy‐dispersive X‐ray analyses led to the full characterization of the SWNTs filled with the CdSe nanocrystals, shedding light on the composition, structure, and electronic interactions of the new nanohybrid materials on an atomic level. A new emerging hybrid nanomaterial, simultaneously filled and beta‐d ‐glucan coated, was obtained by using pristine nanotubes and bulk CdSe powder as starting materials. This displayed fluorescence in water dispersions and unexpected biocompatibility was found to be mediated by beta‐d ‐glucan (a biopolymer extracted from barley) with respect to that of the individual inorganic material components. For the first time, such supramolecular nanostructures are investigated by life‐science techniques applied to functional nanomaterial characterization, opening the door for future nano‐biotechnological applications. Abstract : Crystal clear : Novel water‐dispersible and luminescent carbon‐nanotube‐based hybrids emerge through the filling and confinement of CdSe crystals within single‐walled carbon nanotube cavities of varying dimensions, at elevated temperatures and with the advanced exclusion of air and moisture, followed by their external functionalization with β‐d ‐glucan. Theoretical and experimental studies shed light onto the role of the non‐covalent interactions between the tube walls and the filled crystals, and the energy transfer between the different hybrid components.